Distinctive expression pattern of cystathionine‐β‐synthase and cystathionine‐γ‐lyase identifies mesenchymal stromal cells transition to mineralizing osteoblasts. Issue 12 (27th March 2017) - Gambari, Laura; Lisignoli, Gina; Gabusi, Elena; Manferdini, Cristina; Paolella, Francesca; Piacentini, Anna; Grassi, Francesco
Abstract : Mesenchymal stromal cells (MSCs) are key players in the repair or regeneration of the damaged bone tissue. However, heterogeneity exists between MSCs derived from different donors in their bone formation ability both in vitro and in vivo. The identification of markers defining MSCs with different functional phenotypes is fundamental to maximize their clinical potential. In our previous in vivo study, impaired expression in MSCs of cystathionine‐β‐synthase (CBS) and cystathionine‐γ‐lyase (CSE), the two key enzymes in the catabolic pathway of homocysteine, was associated to decreased bone formation and to the onset of osteoporosis in mice. Here, we investigated whether osteogenic differentiation of human MSCs (hMSCs) modulates the expression of CBS and CSE. The expression of CBS and CSE was also assessed during chondrogenesis to confirm the specificity of their expression during osteogenesis. hMSCs displayed a heterogeneous mineralizing capacity between donors (70% of the samples mineralized, while 30% did not mineralize). Inducible expression of CBS and CSE was found to be associated with a mineralizing phenotype in hMSCs. In particular, up‐regulation of CSE was restricted to hMSCs undergoing mineralization. During chondrogenesis, CBS was significantly up‐regulated while CSE expression was not affected. Ex‐vivo findings confirmed that mature h‐osteoblasts (hOBs) show consistently higher expression of CBS and CSE than hMSCs. Our data provide the first evidence that the expression of CBS and CSE in hMSCs closely correlates with the transition of hMSCs toward the osteoblastic phenotype and that CSE may constitute a novel marker of osteogenic differentiation. Abstract : Human mesenchymal stromal cells (hMSCs) play a pivotal role in the regeneration of bone tissue, but are affected by a marked heterogeneity in functional response to osteogenic stimuli. Inducible expression of CBS and CSE was found to be associated with a mineralizing phenotype in hMSCs and their expression correlates with the transition of hMSCs towards the osteoblastic phenotype. CSE may constitute a novel marker of osteogenic differentiation.